2017
DOI: 10.1371/journal.pone.0174811
|View full text |Cite
|
Sign up to set email alerts
|

The shift from high to low turnover bone disease after parathyroidectomy is associated with the progression of vascular calcification in hemodialysis patients: A 12-month follow-up study

Abstract: Parathyroidectomy (PTX) may cause low levels of PTH, leading to an excessive reduction of bone turnover, which is associated with poor outcomes in dialysis patients, including vascular calcification (VC). We aimed to prospectively investigate the impact of PTX on bone remodeling and its potential consequence on the progression of VC in hemodialysis patients. In this prospective study, 19 hemodialysis patients with severe secondary hyperparathyroidism (sHPT) were evaluated. All patients underwent laboratorial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…An appropriate assessment of preoperative ALP, VDA, and CSR agonist exposure as well as an appropriate cessation of the CSR agonist therapy before surgery may be helpful to avoid the overzealous removal of parathyroid tissues . Persistently low PTH levels with adynamic bone disease confer a potential for increased vascular calcification . The temporary use of synthetic subcutaneous PTH analog therapy has only been reported anecdotally and has not been formally studied in renal patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriate assessment of preoperative ALP, VDA, and CSR agonist exposure as well as an appropriate cessation of the CSR agonist therapy before surgery may be helpful to avoid the overzealous removal of parathyroid tissues . Persistently low PTH levels with adynamic bone disease confer a potential for increased vascular calcification . The temporary use of synthetic subcutaneous PTH analog therapy has only been reported anecdotally and has not been formally studied in renal patients .…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Postoperative hypocalcemia continues to be a concern. 18 Overzealous removal of parathyroid tissues results in suppressed PTH with low turnover or adynamic bone disease 27 as the momentum is already shifting away from overtly aggressive control of PTH levels in ESRD in general. 28,29 One relatively new technology of the recent 2 decades is the intraoperative monitoring of PTH, affording a customized or individualized reduction of the enlarged parathyroid tissues during operations.…”
Section: Introductionmentioning
confidence: 99%
“…High PTH levels drive the indolent OB into high viability and function but poor quality in behaviour, resulting in both bone quality and quantity loss . However, medical or surgical treatment of SHPT which largely remove much of the PTH hypersecretion, the bone cells may return back to the innate low bone cell viability status –the low bone turnover disorders …”
Section: Bone Disorders In Ckdmentioning
confidence: 99%
“…Surgical management of SHPT has, however, failed to demonstrate a protective effect on VC. A recent prospective observational study of 19 hemodialysis patients with severe SHPT reported that parathyroidectomies resulted in increased CAC ( P = .02) and were associated with a shift from high to low bone turnover disease on bone biopsy over a 12‐month period (90% of patients evolved to either very low or low bone turnover) . The presence of low bone turnover disease has previously been associated with a substantially increased risk of VC …”
Section: Current Therapeutic Strategies To Reduce Vcmentioning
confidence: 99%